Blunted diurnal interleukin-6 rhythm is associated with amygdala emotional hyporeactivity and depression: a modulating role of gene-stressor interactions - Hakamata, Yuko; Hori, Hiroaki; Mizukami, Shinya; Izawa, Shuhei; Yoshida, Fuyuko; Moriguchi, Yoshiya; Hanakawa, Takashi; Inoue, Yusuke; Tagaya, Hirokuni (Frontiers in Psychiatry, 2023)
Background The immune system has major roles in the brain and related psychopathology. Disrupted interleukin-6 secretion and aberrant amygdala emotional reactivity are well-documented in stress-related mental disorders. The amygdala regulates psychosocial stress-related interleukin-6 affected by related genes. These led us to comprehensively examine the relationship between interleukin-6, amygdala activity, and stress-related mental symptoms under gene-stressor interactions. Methods One hundred eight nonclinical participants with various levels of anxiety/depression underwent magnetic resonance imaging scans during an emotional face task for amygdala activity and saliva collection (at 10-time points across 2 days) for the total output and diurnal patterns of interleukin-6. Gene-stressor interactions between rs1800796 (C/G) and rs2228145 (C/A) and stressful life events for the biobehavioral measures were explored. Results The blunting of interleukin-6 diurnal pattern was associated with hypoactivation of the basolateral amygdala in response to fearful (vs. neutral) faces (t = 3.67, FWE-corrected p = 0.003), and was predominantly observed in individuals with rs1800796 C-allele homozygotes and negative life changes in the past year (F = 19.71, p < 0.001). When considered in a comprehensive model, the diminished diurnal pattern predicted greater depressive symptoms (β = −0.40), modulated by the amygdala hypoactivity (β = 0.36) and rs1800796-stressor interactions (β = −0.41; all p < 0.001). Conclusion Here we show that the blunted interleukin-6 diurnal rhythm predicts depressive symptoms, modulated by amygdala emotional hyporeactivity and gene-stressor interactions. These findings indicate a potential mechanism underlying vulnerability to depressive disorders, suggesting their early detection, prevention, and treatment through the understanding of immune system dysregulation.